Hiddenness, holiness, and impurity. Issue 2 (28th July 2016) - KYLE, BRENT G.
Abstract: John Schellenberg has advanced the hiddenness argument against God's existence, based on the idea that an all-loving God would seek personal relationships. This article develops a reply to Schellenberg's argument by examining the notion of moral impurity, as understood by Paul the Apostle. Paul conceptualized moral impurity as a causal state that transfers from person to person, like a contagious disease. He also believed that moral impurity precludes divine–human relationship. The goal of this article is to develop these ideas into a problem for one of Schellenberg's key premises.